Plastic culture : - Phoenix, Woodrow (Kodansha International, 2006)
Plastic Culture explores the world of toys: why we love them, what they represent, and why there is a growing market for "designer" and "art" toys aimed at adults." "In this book, British author Woodrow Phoenix takes a look at our relationship to toys in the twenty-first century, with particular reference to Japan - an exporter of both merchandise and ideas. Plastic toys based on Japanese comics, movies, and TV shows, from Astro Boy, Godzilla, and Gatchaman, to Power Rangers, Sailor Moon, and Pokemon have had a powerful effect on the imaginations and markets of the West, and have kick-started trends in design and pop culture that have crossed from Japan to the West and back East again." "Brimming with full-color illustrations of cult and limited-edition toys, and with an in-depth look at the work of Japanese artists Takashi Murakami and Yoshitomo Nara, Hong Kong trendsetters Eric So and Michael Lau, and many other leading players in the world of designer toys, this is a book that will appeal to a wide range of readers: from those interested in the latest trends in contemporary art, to toy collectors, and to anyone with an interest in Japan's influence on contemporary pop culture.